Connectivity of the pedunculopontine nucleus in parkinsonian freezing of gait. - Schweder, P; Hansen, P; Green, A; Quaghebeur, G; Stein, J; Aziz, T (2010)
Parkinson's disease (PD) may involve sudden unintended arrests in gait or failure to initiate gait, known as gait freezing. Deep brain stimulation of the pedunculopontine nucleus (PPN) has been found to be an effective therapy for this phenomenon. In this study, we characterized the connectivity of the PPN freezing of gait (FOG) patients, compared with non-FOG PD and healthy controls using diffusion tensor imaging techniques. Differences in PPN connectivity profiles of the study groups were shown in the cerebellum and pons. The PPN showed connectivity with the cerebellum in controls and non-FOG PD. FOG patients showed absence of cerebellar connectivity, and increased visibility of the decussation of corticopontine fibres in the anterior pons. The findings suggest that corticopontine projections, which cross at the pons are increased in gait freezing, highlighting the importance and role of corticopontine-cerebellar pathways in the pathophysiology of this phenomenon.